Mobile Tourism Research and Practices: A Comprehensive Bibliometric Exploration and Future Study Direction - Syaifullah Syaifullah; Shamsul Arrieya Ariffin; Norhisham Mohamad Nordin (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Even though mobile tourism analysis is developing, there is still a lack of literature regarding its formation patterns which makes the picture of its evolution incomplete. The evaluation in this study was carried out in general by emphasizing the evolution of exploratory analysis on the theme of "mobile tourism". This article aims to determine the increasing development of mobile tourism in terms of the number of publications, journals, authors, and the most relevant citations. Then analyze the itinerant tourism distribution map based on grouping, with merging, joint citation, collaboration network analysis, and joint word assessment, and interpret the conceptual structure of the country's co-occurrence and collaboration network regarding its visual representation. The method used is a descriptive approach through bibliometric analysis. An in-depth search of the Scopus database and RStudio software was conducted, screening, analyzing, and interpreting 752 relevant articles from 2014 to 2023. The findings show that an increase in the development of mobile tourism is identified from an increase in the number of publications, the most relevant journals, and authors, as well as the increasingly diverse origins of the authors even though the number of annual average citations has decreased slightly. Recommended six themes in mobile tourism studies, namely Tourism, Technology Acceptance Models (TAM), Mobile Applications, Recommendation Systems, Loyalty, and Cultural Tourism, and produced Technology Acceptance Models and Tourism as important studies with great prospects in the future.